Effects of cabozantinib on bone turnover markers in real-world metastatic renal cell carcinoma. Issue 6 (December 2021) - Ratta, Raffaele; Verzoni, Elena; Mennitto, Alessia; Pantano, Francesco; Martinetti, Antonia; Raimondi, Alessandra; Sepe, Pierangela; Sottotetti, Elisa; Mennitto, Roberta; Morelli, Daniele; Santini, Daniele; de Braud, Filippo G.; et al.
Background: Cabozantinib strongly inhibits osteoclast differentiation and bone resorption in vitro. We aimed to evaluate its effect on bone turnover markers (BTMs) in metastatic renal cell carcinoma. Methods: This is a monocentric prospective study on patients with mRCC treated with cabozantinib between October 2016 and July 2018. We collected blood samples at baseline and after 3 and 6 months of treatment. We compared sets of data obtained from plasma samples in the whole population with unpaired 2-tailed Student t tests and data for a subset of patients for which all timepoints were available with paired 2-tailed Student t tests. We used the Kaplan-Meier method for survival analyses and the log-rank test to compare the curves. Results: Our analysis included 39 patients. At month 3, the mean C-terminal cross-linked telopeptides of type I collagen (CTx) and the mean N-terminal propeptide of type 1 collagen (PINP) levels were significantly decreased in the whole population ( p = 0.013 and p < 0.0001, respectively), as well as at paired analysis ( p = 0.015 and p = 0.045, respectively). No differences were observed between baseline and 6 months ( p = 0.053 and p = 0.087, respectively). After 3 months, the mean parathyroid hormone (PTH) levels significantly increased in the whole population ( p = 0.004), as well as at paired analysis; the mean PTH levels increased significantly at 3 and 6 months, respectively ( p = 0.019 and p = 0.041, respectively). Changes in BTM levels were not associated with outcome. Conclusions: Cabozantinib significantly reduced bone resorption as demonstrated by the decrease of CTx and showed a transient secondary increase of PTH.